Development of nanoformulation for hyperpigmentation disorders: Experimental evaluations, in vitro efficacy and in silico molecular docking studies - Budama-Kilinc, Yasemin; Gok, Bahar; Kecel-Gunduz, Serda; Altuntas, Ebru (ELSEVIER, 2022)
Hyperpigmentation is a crucial dermatological disorder. This study aims to formulate a nanoemulsion formulation containing chlorogenic acid (CA) for hyperpigmentation treatment, to carry out characterization studies, and to investigate its efficacy and safety in vitro and in silico anal-ysis.In line with this purpose, CA nanoemulsions (CA-NEs) were developed using the ultrasonic homogenization method. Accelerated stability tests were performed to examine the kinetic and ther-modynamic stability of the CA-NEs to ascertain the presence of any stability issues. After the heat-ing-cooling test, appropriate CA-NEs were stored for 60 days in three different stability environments to examine the physicochemical stability and determine the finalized formulation. The toxicity of the finalized CA-NE formulation was evaluated by genotoxicity/mutagenicity and cytotoxicity tests. The tyrosinase and melanogenesis activities of the finalized CA-NE formulation were determined on the Melanoma B16F0 cell line. Finally, the molecular docking method was used to reveal interactions of CA that play an essential role in tyrosinase inhibition. Additionally, the mushroom and human tyrosinase enzymes were used to determine the activity of CA. In addition, the comparison study with the molecular docking method was carried out using kojic acid as a ref - erence molecule. In conclusion, the molecular docking study, pharmacokinetic analyses, and in vitro studies showed that F4P1 coded CA-NE formulation might hold promise as an innovative formulation in cosmetic applications such as skin-lightening effects with its high efficacy and safety profile.(c) 2022 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Chlorogenic acid; Nanoemulsion; Tyrosinase; Melanogenesis; Hyperpigmentation; Molecular docking; MELANOGENESIS INHIBITORS; TYROSINASE ACTIVITY; ACCURATE DOCKING; CINNAMIC ACID; NANO-EMULSION; SKIN; VITRO; OIL; Chemistry